2014
DOI: 10.3390/nu6020637
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Reduces Reaction Time and Improves Performance in Simulated-Contest of Taekwondo

Abstract: The aim of this study was to investigate the effects of caffeine on reaction time during a specific taekwondo task and athletic performance during a simulated taekwondo contest. Ten taekwondo athletes ingested either 5 mg·kg−1 body mass caffeine or placebo and performed two combats (spaced apart by 20 min). The reaction-time test (five kicks “Bandal Tchagui”) was performed immediately prior to the first combat and immediately after the first and second combats. Caffeine improved reaction time (from 0.42 ± 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
102
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 30 publications
11
102
0
3
Order By: Relevance
“…It has been shown to reduce reaction time and delay fatigue in taekwondo [68], improve cycling time trials in triathletes [69], and decrease times in cross country double poling [70]. However, other studies have not shown significant improvement with caffeine.…”
Section: Performancementioning
confidence: 96%
“…It has been shown to reduce reaction time and delay fatigue in taekwondo [68], improve cycling time trials in triathletes [69], and decrease times in cross country double poling [70]. However, other studies have not shown significant improvement with caffeine.…”
Section: Performancementioning
confidence: 96%
“…The ergogenic effects of caffeine have been demonstrated in different sport modalities, namely running [8,9], cycling [10,11], rowing [12], track and field [3], team sports [4], and martial arts [13], among others.…”
mentioning
confidence: 99%
“…27 The ingestion of CAF improved reaction times before the first combat, increased the intensity of round 1, and maintained the intensity observed in the first combat in the second. 27 These findings provide support for the initial performance improvements seen during SPR 1 and SPR 2 in the current study. Participants were able to push faster in the first 2 SPRs, but this led to the development of fatigue, and therefore no further improvements were seen.…”
Section: Sprint Performancementioning
confidence: 90%
“…This corroborates previous research in able-bodied individuals that has shown initial improvements in performance after CAF ingestion with a subsequent null or negative influence on latter bouts. 5,27,28 Faster 30-m-sprint times in the first 3 (of 12) sprints after 5-mg/kg CAF supplementation have been reported. 5 Those authors hypothesized that the mechanism responsible for this initial improvement was a CNS effect mediated by antagonism of adenosine receptors.…”
Section: Sprint Performancementioning
confidence: 93%